Applied Behavior Analysis - Maich, Kimberly; Levine, Darren; Hall, Carmen (Springer, 2016)
The purpose of this publication is to provide ready-to-use case studies to accompany current academic textbooks and field training materials used by students and professionals studying, teaching, and working in the field of Applied Behavior Analysis (ABA). Through 50 case studies, learners are provided opportunities to apply ABA principles, processes, and practices to a range of scenarios across the life span. These scenarios offer a simulated platform for learners to design, implement, and evaluate behavior-change programs for children, adolescents, adults, and seniors across a range of home, school, and community settings. The case studies within this work reflect the field experience of the authors as well as that of the academic faculty, field-based professionals, and students that contributed to the development of this valuable resource. Each case encourages users to reflect on, and think critically about, selected concepts and principles of ABA. When combined, the 50 cases within this text guide learners through the phases of behavior-analytic practice—from assessment and planning through implementation and evaluation—while offering a range of research and ethical considerations central to the science and practice of behavior analysis.
Fifty Case Studies in Home, School, and Community Settings